The effect of scarcity messages in online advertisements to consumer's purchase intention - Bobis, Valerie Lucile Pacis
This is a quasi-experimental research design that determined the effect of varied scarcity messages in online advertisements for bags to the Purchase Intention of consumers. The study used Completely Randomized Groups (CR-k) Post-test only design. A total of 90 undergraduate female students enrolled in the University of the Philippines were selected using a two-stage random sampling where the colleges were clustered and randomly selected using fish bowl method. From the six colleges, classes were pre-selected and only one class was chosen from each college. Then, the respondents were randomly assigned to one of the three experimental groups who received either advertisement with Quantity limit, advertisement with Time limit or advertisement without scarcity message. The respondents voluntarily participated in the study and were presented with fictitious online bag advertisements. In order to reduce extraneous variables, the respondents were given initial assumptions and were allowed to choose the bag that most appealed to them. ANOVA was used in order to test the difference and interpret the results of the Purchase Intention Scores. The results revealed that the respondents who read the advertisement without scarcity message indicated higher Purchase Intention mean scores compared with the two groups who were presented with scarcity message (Quantity and Time limit). In addition, ANOVA results showed that no significant difference among the three product advertisements with varied scarcity messages in terms of Purchase Intention of consumers to bags without perceived unique-value or elite value item may no be an effective marketing tool. It would be interesting to study the influence of scarcity messages for rare and elite brand merchandise. Future studies also should extend this research by using other products that are for sale online aside from fashion items by using pre-selection of respondents to know that they are really interested in the products.